Pengembangan Media Pembelajaran Flipbook Kisah Keteladanan Walisongo untuk Meningkatkan Minat Belajar Siswa di MTsN 1 Jombang - Anggraeni, Nisa Lailatul; Rahmawati, Rina Dian (YASIN, 2025)
This study aims to design and develop learning media in the form of flipbooks and test their feasibility, practicality, and readability on the material of the Walisongo Exemplary Stories at MTs Negeri 1 Jombang. This study uses the Research and Development (R & D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, evaluation. The study was conducted in November 2024 with its feasibility first tested by 1 material expert lecturer, 1 media expert lecturer, and grade IX students. Data were collected through interviews and assessment questionnaires from experts, teachers, and students. The results of the study revealed that the flipbook media provided significant results obtaining a score of 86% from material validation and 83% from media validation, both in the "Very Feasible" category. After validation by material experts and media experts, the flipbook was then tested on a small and large scale. The readability test on a small scale for teachers reached 89% and students 83%, both in the "Very Good" category. Meanwhile, the small-scale practicality test on teachers obtained 91% and students 83%, so it was categorized as "Practical." The large-scale test showed a readability of 83% ("Very Good") and practicality of 84% ("Practical"). Based on these results, flipbook-based learning media are declared feasible and practical to use at MTs Negeri 1 Jombang.